Individual and contextual factors associated with childhood stunting in Nigeria: a multilevel analysis. Issue 2 (18th October 2011) - Adekanmbi, Victor T.; Kayode, Gbenga A.; Uthman, Olalekan A.
Abstract Stunting, a form of undernutrition, is the best measure of child health inequalities as it captures multiple dimensions of children's health, development and the environment where they live. The aim of this study was to quantify the predictors of childhood stunting in Nigeria. This study used data obtained from the 2008 Nigeria Demographic and Health Survey (NDHS). A total of 28 647 children aged 0–59 months included in NDHS in 2008 were analysed in this study. We applied multilevel multivariate logistic regression analysis in which individual‐level factors were at the first level and community‐level factors at the second level. The percentage change in variance of the full model accounted for about 46% in odds of stunting across the communities. The present study found that the following predictors increased the odds of childhood stunting: male gender, age above 11 months, multiple birth, low birthweight, low maternal education, low maternal body mass index, poor maternal health‐seeking behaviour, poor household wealth and short birth interval. The community‐level predictors found to have significant association with childhood stunting were: child residing in community with high illiteracy rate and North West and North East regions of the country. In conclusion, this study revealed that both individual‐ and community‐level factors are significant determinants of childhood stunting in Nigeria.